Analisis Putusan Hakim Pengadilan Agama Solok Tentang Asal Usul Anak dan Relevansinya dengan Maqashid Syariah - Irvan Refliandi; Mona Eliza (IDRIS Darulfunun Institute, 2023)
The next generation of nations, which includes children, will alter the course of global civilization. Since blood links are the primary source of family relationships because they serve as the family's